Cardiac Cell Senescence and Redox Signaling - Cesselli, Daniela; Aleksova, Aneta; Sponga, Sandro; Cervellin, Celeste; Di Loreto, Carla; Tell, Gianluca; Beltrami, Antonio Paolo (Frontiers in Cardiovascular Medicine, 2017)
Aging is characterized by a progressive loss of the ability of the organism to cope with stressors and to repair tissue damage. As a result, chronic diseases, including cardiovascular disease, increase their prevalence with aging, underlining the existence of common mechanisms that lead to frailty and age-related diseases. In this frame, the progressive decline of the homeostatic and reparative function of primitive cells has been hypothesized to play a major role in the evolution of cardiac pathology to heart failure. Although initially it was believed that reactive oxygen species (ROS) were produced in an unregulated manner as a byproduct of cellular metabolism, causing macromolecular damage and aging, accumulating evidence indicate the major role played by redox signaling in physiology. Aim of this review is to critically revise evidence linking ROS to cell senescence and aging and to provide evidence of the primary role played by redox signaling, with a particular emphasis on the multifunctional protein APE1/Ref in stem cell biology. Finally, we will discuss evidence supporting the role of redox signaling in cardiovascular cells.